2016
DOI: 10.1002/ejic.201601053
|View full text |Cite
|
Sign up to set email alerts
|

Structural Arrangement of 4‐[4‐(Dimethylamino)phenylazo]pyridine Push–Pull Molecules in Acidic Layered Hosts Solved by Experimental and Calculation Methods

Abstract: 4‐[4‐(dimethylamino)phenylazo]pyridine (further denoted as G) representing a type of push–pull molecules can be intercalated into α‐ and γ‐modifications of zirconium phosphate (α‐ZrP and γ‐ZrP) and into zirconium (4‐sulfophenyl)phosphonate (ZrSPP). The obtained intercalates form single phases with interlayer distances of 12.75, 16.31, and 24.11 Å for α‐ZrP·0.2G·1.5H2O, γ‐ZrP·0.2G·1.5H2O, and ZrSPP·0.5G·1H2O, respectively. The increase of the interlayer distance upon intercalation suggests that the molecules of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…27−30 However, 191 the generation of diazonium salt by aqueous HBF 4 + NaNO 2 192 produces the N-asymmetric azabenzenes in high yields. 31 The 193 structure of 5 was confirmed by single-crystal diffraction (see 194 the Supporting Information). Surprisingly, functionalization of 195 5 with a diethyl-phosphonate group was unsuccessful via either 196 Pd-catalyzed Hirao or Ni-catalyzed coupling.…”
mentioning
confidence: 96%
“…27−30 However, 191 the generation of diazonium salt by aqueous HBF 4 + NaNO 2 192 produces the N-asymmetric azabenzenes in high yields. 31 The 193 structure of 5 was confirmed by single-crystal diffraction (see 194 the Supporting Information). Surprisingly, functionalization of 195 5 with a diethyl-phosphonate group was unsuccessful via either 196 Pd-catalyzed Hirao or Ni-catalyzed coupling.…”
mentioning
confidence: 96%
“…In this arena, cointercalation of a suitable donor and acceptor pair which involves donor-to-acceptor (D−A) energy transfer and intercalation of the donor−pi−acceptor (D−π−A) system which involves internal charge transfer (ICT) are the two most dominant modes of energy transfer within the ZrP gallery. 102,129,139 4.2.1. Donor-to-Acceptor Energy Transfer Inside Zirconium Phosphate Gallery.…”
Section: Intercalation Of Zirconium Phosphatementioning
confidence: 99%
“…Melanova et al investigated the structural arrangement of 4-[4-(N,N-dimethylamino) phenylazo]pyridine-based push− pull system into the gallery of αand γ-ZrP. 129 TGA and molecular simulations are consistent with parallel (head-to-tail) orientation of guest molecules inside the ZrP gallery for the generation of molecular dipoles. The same research group reported the first of its kind intercalation and ICT enhancement of tripodal tris[(pyridine-4-yl)-phenyl]amine (TPPA) push− pull system inside αand γ-ZrP.…”
Section: Intercalation Of Zirconium Phosphatementioning
confidence: 99%
See 1 more Smart Citation
“…Herein we have designed a push–pull dye having 4,5-bis­[4-( N , N -dimethylamino)­phenyl]­imidazole as the donor moiety and 4,5-dicyanoimidazole as the acceptor unit (Figure c). The polarizability of such D−π–A system depends on the chemical structure, particularly on the electronic characteristics of the donor and acceptor moiety, overall geometry, and length of the π-conjugated linker . Thus, these compounds find tremendous applications as active parts of light-emitting diodes, optoelectronic devices, and organic photovoltaic cells, etc .…”
Section: Introductionmentioning
confidence: 99%